2000
DOI: 10.1023/a:1008307528519
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine for relapsed or resistant lymphoma

Abstract: Gemcitabine has substantial activity and acceptable toxicity in heavily pre-treated patients with advanced lymphoma. Further study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…Preliminary evidence of single-agent efficacy and satisfactory tolerability for gemcitabine against relapsed and refractory lymphoma has seen it incorporated into treatment combinations. 15,16 Combination therapy with vinorelbine and gemcitabine has been found to be effective in the management of advanced nonsmall cell lung cancer, 17 and we have previously shown that the combination of vinorelbine and gemcitabine is an effective and tolerable salvage approach for both NHL and HL with overall response rates of 70%, and 47%, for patients in first relapse or with more advanced disease, respectively. 18 Combinations of gemcitabine and vinorelbine with liposomal doxorubicin (GND) have been used successfully for the salvage of Hodgkin disease.…”
mentioning
confidence: 99%
“…Preliminary evidence of single-agent efficacy and satisfactory tolerability for gemcitabine against relapsed and refractory lymphoma has seen it incorporated into treatment combinations. 15,16 Combination therapy with vinorelbine and gemcitabine has been found to be effective in the management of advanced nonsmall cell lung cancer, 17 and we have previously shown that the combination of vinorelbine and gemcitabine is an effective and tolerable salvage approach for both NHL and HL with overall response rates of 70%, and 47%, for patients in first relapse or with more advanced disease, respectively. 18 Combinations of gemcitabine and vinorelbine with liposomal doxorubicin (GND) have been used successfully for the salvage of Hodgkin disease.…”
mentioning
confidence: 99%
“…Preclinical studies of gemcitabine and cisplatin have demonstrated synergy both in vitro and in vivo (Peters et al, 1995). Phase I studies evaluating this combination in relapsed and refractory HL and NHL have also reported higher RRs (Aviles et al, 2004;Emmanouilides et al, 2004) compared to either agent given as monotherapy (Fossa et al, 1999;Santoro et al, 2000;Savage et al, 2000;Zinzani et al, 2000). The mechanisms underlying this synergy may be due to increased incorporation of gemcitabine into DNA and RNA, and increased cisplatin -DNA adduct formation by inhibition of exonuclease and DNA repair (van Moorsel et al, 1999).…”
mentioning
confidence: 99%
“…9). Gemcitabine is another new agent that has been studied in patients with indolent (25) and aggressive (26,27) relapsed or refractory NHL. Although the overall response rate was slightly higher than with SAM486A, gemcitabine was associated with a higher level of toxicity, especially hematological toxicity.…”
Section: Discussionmentioning
confidence: 99%